THE POST-EARNINGS ANNOUNCEMENT DRIFT: DOES IT STILL EXIST IN THE FINNISH STOCK MARKET - Kinnunen, Ville (My University, 2019)
The main purpose of this thesis is to investigate whether the post-earnings announcement drift exists in the Finnish stock market. Additionally, this thesis seeks to find out do illiquid stocks experience a greater post-earnings announcement drift than liquid stocks. Previous studies focusing on the Finnish market have only discovered a negative drift following a negative earnings announcement. Post-earnings announcement drift is one of the oldest and persisting anomalies in the world and it was introduced by Ball & Brown (1968). The post-earnings announcement drift is the tendency for stock prices to drift toward the direction of the earnings surprise for many days. This study conducts an event study to investigate two event windows of [-5,1] and [-1,5] days and see if abnormal returns occur around the interim reports. The data of this thesis includes 41 companies that were listed on the Helsinki stock exchange during the sample period of 2010Q2 to 2017Q2. The results show that there is a positive drift that lasts from three days before the announcement day to two days after that. On the contrary to earlier studies, the negative drift seems to dissipate after the announcement day. Illiquid stocks were found to exhibit a positive drift that was greater in magnitude than in liquid stocks for -2 to +1 days around the event day, while negative drift for illiquid stocks was only greater after the announcement day.
Keywords: Post-Earnings Announcement Drift; Anomaly; Efficient markets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|